PIEZO1 acts as a cancer suppressor by regulating the ROS/Wnt/β‐catenin axis - Haimei Bo; Qi Wu; Chaonan Zhu; Yang Zheng; Guang Cheng; Lihua Cui (Thoracic Cancer, 2024)
Abstract Background PIEZO1 works differently in different cancers and at different stages of development. The objective of the current study was to explore the function and underlying mechanism of PIEZO1 in lung adenocarcinoma (LUAD) cells. Methods Different LUAD cell lines were treated with PIEZO1 inhibitor (GsMTx4) and agonist (Yoda1), and the expression of PIEZO1 in LUAD cells was detected using real‐time quantitative PCR (RT‐qPCR) and western blotting. The effects of PIEZO1 on invasion, migration and epithelial‐mesenchymal transition (EMT) markers protein expression of LUAD cells were detected using the MTT assay, flow cytometry, transwell assay, wound‐healing assay, and western blotting. Reactive oxygen species (ROS) agonists (BAY 87–2243) and inhibitors (NAC) and Wnt/β‐catenin pathway inhibitors (iCRT3) were selected to treat A549 cells to investigate the mechanism of PIEZO1 on ROS production and Wnt/β‐catenin expression in A549 cells. Results In A549, NCI‐H1395, and NCI‐H1975 cells, GsMTx4 promoted cell proliferation, invasion, migration, upregulated EMT‐related marker protein expression, and inhibited cell apoptosis, while Yoda1 exerted effects opposite to those of GsMTx4. In A549 cells, GsMTx4 can reduce ROS production, it also inhibited ROS production, apoptosis, and downregulated proapoptotic markers induced by BAY 87–2243. Importantly, BAY 87–2243 blocked the effect of GSMTX4‐induced Wnt/β‐catenin overexpression. Similarly, Yoda1 can reduce the effect of NAC. In addition, iCRT3 can block the upregulation of EMT‐related marker proteins by GsMTx4, and increase apoptosis and decrease cell invasion and migration. Conclusion In summary, PIEZO1 acts as a cancer suppressor by regulating the ROS/Wnt/β‐catenin axis, providing a new perspective on the role of mechanosensitive channel proteins in cancer.